Intention to Become Digital Startups - Wornchanok Chaiyasoonthorn (My University, 2019)
This research aims to study the intention to become digital startups and to explore factors affecting the motivation of being digital startups.The theory of planned behavior (Ajzen's model) was operationalized to predict intention to become digital startups.The sample in this research is 400 undergraduate students in Thailand which were selected by using a convenience sampling method.The multiple linear regression was used for hypothesis testing.Research findings indicate that attitude toward the behavior, subjective norm, and perceived behavioral control positively affects the intention to become digital startups.The most significant variable in predicting the intention is the subjective norm while perceived behavioral control and attitude toward the behavior follow.The contributions of this study encourages people who intend to be a startup joining training programs and surrounding social norm such as mentor, role model, and significant others will leverage more intention to become digital startups.
Keywords: Entrepreneurship Studies and Influences